Tác động của DESG đến ý định mua của người tiêu dùng Việt Nam trong ngành thực phẩm và đồ uống: Vai trò trung gian của truyền miệng điện tử - Nguyễn Ngọc , Sơn; Trần Bảo , Trâm; Đào Thu, Trang; Lê Thị Ngọc , Linh; Nguyễn Như, Quỳnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study aims to determine the impact of Digital ESG (DESG) including Digital Environmental, Social, and Governance on consumer purchase intention through the mediating role of the EWOM. These relationships are confirmed with 721 people who participated in our survey. The results of SEM analysis not only show that the model fits well with research data but also verify the significant influence of DESG in forming the consumers’ intentions. The results also validate the mediating power of the EWOM in the Vietnam context. Surprisingly, the results show that DESG has both a direct impact on consumer purchase intention as well as an indirect impact through electronic word of mouth (EWOM). These findings help policymakers make necessary suggestions to promote consumer purchase intention in the digitalization era.